19. ASSESSMENT OF HOOKWORM INFECTION AND ASSOCIATED FACTORS IN PATIENTS WITH EOSINOPHILIA AT THUAN AN CITY MEDICAL CENTER, BINH DUONG PROVINCE, VIETNAM (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of hookworm infection and the factors related to infection in eosinophilia patients at Thuan An Medical Center, Binh Duong province.Subjects and methods: A cross-sectional descriptive study was conducted on 137 patients with eosinophilia (≥ 300 cells/mm³) at Thuan An Medical Center, Binh Duong province. Stool samples were processed using fresh stool microscopy and Willis concentration technique to identify hookworm infection status and analyze the factors related to infection.Results: The prevalence of hookworm infection among patients with eosinophilia was 8%. Associated factors included agricultural occupation, educational level, barefoot walking, direct soil contact with bare hands, irregular use of anthelmintic drugs, gastrointestinal symptoms, anemia, hemoglobin concentration, and platelet count. Multivariate regression analysis identified anemia and soil exposure associated with hookworm infection.Conclusion: In the study population, 8% of patients with eosinophilia were identified as infected with hookworms, indicating that the risk of transmission remains present in the surveyed area. Interventions targeting risk behaviors such as walking barefoot, direct contact with soil, and irregular use of deworming medication, along with enhanced screening for anemia, are essential for early detection and effective control of hookworm infections.
Keywords: Hookworm, eosinophilia, associated factors, Binh Duong.